Sosialisasi pembuatan sabun cuci piring dari minyak jelantah sebagai solusi permasalahan limbah rumah tangga serta mengatasi kemiskinan pada masyarakat Desa Madyocondro, Kecamatan Secang, Kabupaten Magelang - Anggraeni, Septia Ade; Tristiany, Risma Ully; Shofiyah, Siti; Khasanah, Ulkhiatun; Azizah, Wilujeng Lu’lu’ Nur (Nur Science Institute, 2024)
Used cooking oil has long been a household waste that is left unutilized, which can lead to environmental pollution. This activity aims to provide education and skills in making dishwashing soap from used cooking oil waste. The community service was conducted in Catak Madyocondro Hamlet, Secang, Magelang. The activity was carried out in the form of direct training for members of the Family Welfare Program (PKK) and housewives residing in the area. The soap made from used cooking oil was then tested for its foaming ability and cleaning effectiveness. The dishwashing soap-making training received a positive response. It provided both knowledge and skills to the residents of Catak Hamlet in processing used cooking oil waste into dishwashing soap that is safe to use.